Metodología para valoración financiera de Pymes colombianasutilizando flujos de efectivo1 (2018)
In this paper a model is designed and developed to value financially small and medium enterprises (SME’s) in Colombia, which are operating and that are not publicly traded. The Discounted Cash Flow methodology is used, which uses historical financial statements as input, such as the Balance Sheet, the Income Statement and the Free Cash Flow Statement the inclusion of some macroeconomic variables and an appropriate discount rate, to be able to estimate the present values of both the projected Free Cash Flows and the residual value of the company, which are used to determine the Total Financial Value of a SME, and becomes key information for making financial decisions before a possible negotiation of purchase o sale.